Lung cancer and aortic stenosis: one-stage surgical treatment - A. A. Pechetov; B. G. Alekyan; A. N. Lednev; M. A. Makov; N. G. Karapetyan; L. G. Gelecyan (Вестник хирургии имени И.И. Грекова)
Surgical treatment of oncological diseases with concomitant somatic pathologies is a complex issue. In situations when concomitant somatic pathology also requires a surgical approach, the determination of adequate treatment tactics is most relevant. Delayed surgical treatment of cancer increases the risks of progression and generalization of the process; surgical treatment of a tumor against the background of decompensated concomitant pathology potentially entails risks of an unfavorable outcome. With a combination of oncological and somatic diseases, the definition of treatment algorithms today is one of the primary tasks.This paper presents a clinical observation of one-stage surgical treatment of lung cancer and severe aortic stenosis, provides a brief literature review on this topic.